Effectiveness and acceptability of home use of misoprostol for medical abortion up to 10 weeks of pregnancy - Volodymyr Podolskyi; Kristina Gemzell‐Danielsson; Lena L. Maltzman; Lena Marions (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The administration of mifepristone, followed by misoprostol, is widely used for medical abortion. Many studies have demonstrated home abortion to be safe in pregnancies up to 63 days of gestation, and recent data support its safety when extended to more advanced pregnancies. We studied the efficacy and acceptability of home use of misoprostol up to 70 days of gestation in a Swedish setting and compared the outcomes between pregnancies with a gestational age of up to 63 days and pregnancies with gestational age 64–70 days. Material and methods This prospective cohort study was performed between November 2014 and November 2021 at Södersjukhuset and Karolinska University Hospital, Stockholm, and some patients were also recruited from Sahlgrenska University Hospital, Göteborg and Helsingborg Hospital. The primary outcome was the rate of complete abortions and was defined as complete abortion without any need for surgical or medical intervention and assessed by clinical assessment, pregnancy test and/or vaginal ultrasound. Secondary objectives were assessed by daily self‐reporting in a diary and included pain, bleeding, side effects and women's satisfaction and perception of home use of misoprostol. A comparison of categorical variables was made with Fisher's exact test. The significance level was set to a p‐value ≤0.05. The study was registered at Clinicaltrials.gov on July 14, 2014 (NCT02191774). Results During the study period we enrolled 273 women opting for medical abortion with home use of misoprostol. In the early group, up to 63 days of gestation, 112 women were included with a mean gestational length of 45 days and in the late group, 64–70 days of gestation, 161 women with a mean gestations length of 66.3 days were included. Complete abortion occurred in 95% (95% CI 89–98) of women in the early group and in 96% (95% CI 92–99) in the late group. No differences were found regarding side effects and acceptability was similarly high in both groups. Conclusions Our results show high efficacy and acceptability of medical abortion when misoprostol is administered at home up to 70 days of gestation. This supports previous findings about maintained safety when misoprostol is administered at home even past a very early pregnancy.